Análise de redes sociais informais e o compartilhamento do conhecimento organizacional - Silva, Angelita Freitas da (2010)
The present work search to analyze the structure and the positioning of the actors of the social informal networks in the section of electronics of the Empresa Eliseu Kopp & Co. Ltd., to end to understand how it happens the sharing of the organizational knowledge. For this evaluation, it made use of a research descriptive, qualitative, accomplished through a case study. It is pointed out that qualitative methodologies were used for data collection and analysis of results, but the assessment of social networks requires the involvement in the measurement of quantitative aspects of relationships. To map the informal networks of the sector analyzed were questioned the 27 employees of the sector and; two managers were interviewed in order to identify incentive actions to the sharing of the knowledge existent in the Company. Friendship (KUIPERS apud MACAMBIRA, 2009) and advice (KRACKHARDT and HANSON, 1993) networks were mapped, using a questionnaire adapted from Silva (2003) and Macambira (2009). It was evaluated the structure of networks as Scott (2000) and identified the critical players and the roles assumed according to the classification of Cross and Prusak (2002 apud SANTOS and BASTOS, 2007). To identify incentive actions to the sharing of the knowledge existent in the Company, it made based on Terra (2000) and Nonaka and Takeuchi (1995). Information related to informal social networks were treated in parallel to UCINET program and NETDRAW program, which allowed a view of the characteristics of the networks analyzed. The main results state that the networks studied have a size of 124 relationships (friendship) and 110 relations (advice), low density (5 to 6%), indicating a high potential for relationships to be developed. It is possible to affirm that the main critical actors of the two nets are Turquesa (in the roles of central connector and broker transactional content) and Rubi e Tarsito (as expander borders). On incentive actions to the sharing of the knowledge existent in the Company, it was verified that actions exist in all of the appraised dimensions, however most of them happens in a no-planned way. It emphasize the mapping and analysis of the informal networks allow the location and visualization in a clearer view of who are the critical players and the paths the organizational knowledge, facilitating the sharing of knowledge.